Challenges of Cardiovascular Risk Assessment in the Routine Rheumatology Outpatient Setting: An Observational Study of 110 Rheumatoid Arthritis Patients. Issue 5 (23rd April 2013) - Gossec, L.; Salejan, F.; Nataf, H.; Nguyen, M.; Gaud‐Listrat, V.; Hudry, C.; Breuillard, P.; Dernis, E.; Boumier, P.; Durandin‐Truffinet, M.; Fannius, J.; Fechtenbaum, J.; et al.
Abstract Objective An annual assessment of cardiovascular (CV) risk factors in rheumatoid arthritis (RA) is recommended, but its practical modalities have not been determined. The objective was to assess the feasibility and usefulness of a standardized CV risk assessment in RA, performed by rheumatologists during outpatient clinics. Methods We used a cross‐sectional design within a network of rheumatologists. Each rheumatologist included 5 consecutive unselected patients with definite RA. Data collection included standardized assessment of CV risk factors: blood pressure, interpretation of glycemia and of lipid levels, and calculation of the Framingham CV risk score. Outcome criteria included feasibility (missing data and time taken to assess the patients) and usefulness (the CV risk assessment was considered useful if at least 1 modifiable and previously unknown CV risk factor was evidenced). Results Twenty‐two rheumatologists (77% in office‐based practice) assessed 110 RA patients. The mean ± SD age was 57 ± 10 years, and the mean ± SD RA duration was 11 ± 9 years; 50 patients (45%) were treated with biologic agents, and 76% were women. Regarding feasibility, missing data were most frequent for glycemia (27% of patients) and cholesterolemia (14% of patients). The mean ± SD duration of the CV risk assessment was 15 ± 5 minutes. The CV risk assessment was considered useful in 33 patients (30%), evidencing dyslipidemia (15% of patients) or high blood pressure (9% of patients) as the most frequently previously unknown CV risk factor. Conclusion The assessment of CV risk factors is feasible, but labor intensive, during an outpatient rheumatology clinic. This assessment identified modifiable CV risk factors in 30% of the patients. These results suggest that RA patients are not sufficiently assessed and treated for CV risk factors.